UNIFEM publishes new source books - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Oil Extraction, Fruit and Vegetable Processing, Cereal Processing, Fish processing have all been published in both English and French. Portuguese translations are being prepared.